7 Assessing melanoma BRAF status through ddPCR of cfDNA. Issue 1130 (21st November 2019) - Passy, Lauren; Silva, Shobha; Brock, Ian; Wells, Greg; Cox, Angela; Danson, Sarah
Abstract: Introduction: Treatment of recurrent and metastatic melanoma has been revolutionised by targeted therapy. Inhibitors of mutant BRAF are a systemic treatment offered for patients with stage III/IV melanoma who are known to carry a mutation in BRAF. Currently patients' BRAF mutation status is assessed through molecular analysis of tissue specimens. Cell-free DNA (cfDNA) released from tumours can be used to non-invasively detect active disease and predict survival in melanoma. cfDNA also provides a method for detecting BRAF mutations. This project aimed to ascertain BRAF mutation status in cfDNA through digital droplet PCR (ddPCR) of plasma samples from patients with melanoma. We aimed to assess the relationship between cfDNA BRAF positivity and disease relapse and progression. Methods: Plasma from 100 patients with active or recently resected melanoma was obtained during previous work. 85 samples had cfDNA extracted. Tissue BRAF status was known for 57 samples. cfDNA was extracted from 1–2 ml plasma with the QIAamp circulating nucleic acid kit (QIAGEN®) following manufacturer protocol, eluting cfDNA into 100µL. cfDNA was quantified with SYBR green quantitative real-time PCR (Life Technologies), based on an 87bp GAPDH gene amplicon. ddPCR™ was performed using the Bio-Rad QX200 Droplet Generator™ and Droplet Reader as per manufacturer protocol. Analysis was performed with Bio-Rad QuantaSoft Version 1.7.4. Results: Median yield of cfDNA extracted from 85 samples was 1.97 ng/ml when eluted into 100µL. This was well-correlated with previous cfDNA extraction yields from this sample set (Pearson's r=0.6687, p<0.0005), where a 200µL elution volume was used. 74 samples yielded >10, 000 droplets and were included for analysis. 12 samples contained BRAF mutant positive droplets. A 74% concordance rate between tissue BRAF mutation status and the presence/absence of cfDNA BRAF mutant positive droplets was found. 7/18 tissue BRAF mutant samples contained BRAF mutant droplets, in comparison to 2/32 tissue BRAF wild-type samples. The presence of BRAF mutant positive droplets was significantly different between the tissue BRAF mutant and tissue BRAF wild-type groups (χ2 8.3145, p=0.004). Fractional abundance of BRAF mutant droplets in the samples containing mutant droplets ranged from 0.07–0.74%. When comparing BRAF mutant droplet-containing samples and samples without BRAF mutant droplets, there was no significant difference in rate of relapse (χ2 0.0948, p=0.758), nor mortality rate (χ2 3.3959, p=0.654). Conclusion cfDNA provides a non-invasive snapshot of the tumour genome and any potential therapeutic targets held within. This work demonstrates that a very low volume of cfDNA can be used to detect BRAF mutations in patients with melanoma through ddPCR. Previous work assessing BRAF status in cfDNA has used larger volumes of cfDNA. Though our concordance rates are comparable with other studies, it is possible that using a smaller amount of cfDNA in our ddPCR has resulted in some samples being below the limit of detection for ddPCR. Longitudinal study is warranted to monitor cfDNA BRAF status and mutant fractional abundance, and whether this better correlates with relapse of disease and disease progression.